Diversity and Geographic Distribution of Microsymbionts Associated With Invasive Mimosa Species in Southern China - Xiaoyun Liu; Shenghao You; Huajie Liu; Baojuan Yuan; Haoyu Wang; Euan K. James; Fang Wang; Weidong Cao; Zhong Kuan Liu (Frontiers in Microbiology, 2020)
In order to investigated diversity and geographic distribitution of rhizobia associated with invasive Mimosa species, Mimosa nodules and soils around the plants were sampled from five provinces in southern China. In total, 361 isolates were obtained from Mimosa pudica and Mimosa diplotricha in 25 locations. A multi-locus sequence analysis (MLSA) including 16S rRNA, atpD, dnaK, glnA, gyrB, and recA identified the isolates into eight genospecies corresponding to Paraburkhleria mimosarum, Paraburkholderia phymatum, Paraburkholeria carbensis, Cupriavidus taiwanensis, Cupriavidus sp., Rhizobium altiplani, Rhizobium mesoamericanum, and Rhizobium etli. The majority of the isolates were Cupriavidus (62.6%), followed by Paraburkholderia (33.5%) and Rhizobium (2.9%). Cupriavidus strains were more predominant in nodules of M. diplotricha (76.2) than in M. pudica (59.9%), and the distribution of P. phymatum in those two plant species was reverse (3.4:18.2%). Four symbiotypes were defined among the isolates based upon the phylogeny of nodA-nifH genes, represented by P. mimosarum, P. phymatum–P. caribensis, Cupriavidus spp., and Rhizobium spp. The species affiliation and the symbiotype division among the isolates demonstrated the multiple origins of Mimosa rhizobia in China: most were similar to those found in the original centers of Mimosa plants, but Cupriavidus sp. might have a local origin. The unbalanced distribution of symbionts between the two Mimosa species might be related to the soil pH, organic matter and available nitrogen; Cupriavidus spp. generally dominated most of the soils colonized by Mimosa in this study, but it had a particular preference for neutral-alkaline soils with low fertility whereas. While Paraburkholderia spp. preferred more acidic and fertile soils. The Rhizobium spp. tended to prefer neutral–acidic soils with high fertility soils.